“She was quite capable of asserting herself”: Powerful Speech Styles and Assessments of Credibility in a Sexual Assault Trial - Hildebrand-Edgar, Nicole; Ehrlich, Susan (Language and Law / Linguagem e Direito, 2017)
In this article, we are interested in the relationship between linguistic style and credibility in the legal system as it pertains to the testimony of a complainant and an accused in a Canadian rape trial, R v. Wagar. While Conley and O’Barr’s pioneering work on this topic argued that powerful and assertive speech styles were more credible than powerless and deferential styles in the courtroom, we suggest that these kinds of indexical associations are neither stable nor monolithic across a speech community. Indeed, in the sexual assault trial we examine here, the complainant’s powerful speech style seemed to undermine her credibility because she was perceived to be too ‘assertive’ to be a victim. We argue that the complainant was caught between two paradoxical ideologies: although a powerful speech style, in line with Conley and O’Barr’s claims, may be associated with credibility in the courtroom, the witness’s use of such a style was regarded as inconsistent with her status as a victim of sexual assault. Thus, this paper builds on work that examines the real-world effects of linguistic styles in the courtroom, attending in particular to how certain styles come to be favoured in specific (e.g., gendered) contexts.